Copper inks for printed electronics: a review. Issue 43 (27th October 2022) - Zeng, Xianghui; He, Pei; Hu, Minglu; Zhao, Weikai; Chen, Huitong; Liu, Longhui; Sun, Jia; Yang, Junliang
Abstract : This review summarizes the development of copper inks in printing electronics, including classification of inks, printing and sintering methods, antioxidant strategies, and applications for flexible electronics. Abstract : Conductive inks have attracted tremendous attention owing to their adaptability and the convenient large-scale fabrication. As a new type of conductive ink, copper-based ink is considered to be one of the best candidate materials for the conductive layer in flexible printed electronics owing to its high conductivity and low price, and suitability for large-scale manufacturing processes. Recently, tremendous progress has been made in the preparation of cooper-based inks for electronic applications, but the antioxidation ability of copper-based nanomaterials within inks or films, that is, long-term reliability upon exposure to water and oxygen, still needs more exploration. In this review, we present a comprehensive overview of copper inks for printed electronics from ink preparation, printing methods and sintering, to antioxidation strategies and electronic applications. The review begins with an overview of the development of copper inks, followed by a demonstration of various preparation methods for copper inks. Then, the diverse printing techniques and post-annealing strategies used to fabricate conductive copper patterns are discussed. In addition, antioxidation strategies utilized to stabilize the mechanical and electrical properties of copper nanomaterials are summarized. Then the diverse applications of copper inks for electronic devices, such as transparent conductive electrodes, sensors, optoelectronic devices, and thin-film transistors, are discussed. Finally, the future development of copper-based inks and the challenges of their application in printed electronics are discussed.